WHAT MOST INFLUENCES ON MUDHARABAH DEPOSIT IN INDONESIAN ISLAMIC COMMERCIAL BANKS? - Lilis Renfiana (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
Public interest in investing their funds as a third party is a factor that plays an important role in the development of Islamic banks in Indonesia. One of them is mudharabah deposits. Mudharabah deposits are one of the third party fund raising products at Islamic banks which have the largest amount of funds compared to other fund raising products. This study aims to determine the factors that affect the level of deposits at Islamic Commercial Banks in Indonesia in the 2011-2020 period. This study uses secondary data in the form of BUS financial statements published on the Bank Indonesia website. The sample in this study is 6 BUS which publish their financial statements to BI in the 2011-2020 period. The analysis in this study uses multiple linear regression analysis. The results of this study indicate that the variable amount of profit sharing for Islamic banks has a significant effect on mudharabah deposits. Variables Inflation and Interest Rates have no significant effect on mudharabah deposits.